Comparative Efficacy and Safety of Advanced Intravitreal Therapeutic Agents for Noninfectious Uveitis: A Systematic Review and Network Meta-Analysis - Liao, Weiting; Zhong, Zhenyu; Su, Guannan; Feng, Xiaojie; Yang, Peizeng (Frontiers in Pharmacology, 2022)
Background: To compare efficacy and safety of advanced intravitreal therapeutic regimens including dexamethasone implant, 350 µg and 700 µg; fluocinolone acetonide (FA) implant, 0.2 µg/day, 0.59 mg and 2.1 mg; intravitreal bevacizumab, 1.25 mg; intravitreal ranibizumab, 0.5 mg; intravitreal triamcinolone acetonide (IVTA), 2 mg and 4 mg; and standard of care (SOC, systemic therapy) for non-infectious uveitis. Methods: We searched Cochrane Library database, EMBASE, Medline, clinicaltrials.gov until April, 2021 with 13 RCTs (1806 participants) identified and conducted pair-wise and Bayesian network meta-analysis with random effects. Results: No specific regimen showed a statistically significant advantage or disadvantage to another treatment regimen with regard to efficacy. However, FA implant, 0.59 mg was associated with higher risk of cataract (RR 4.41, 95% CI 1.51 to 13.13) and intraocular pressure (IOP) rises (RR 2.53 95% CI 1.14 to 6.25) compared with SOC at 24 months. IVTA, 4 mg at 6 months was associated with lower risk of IOP rising compared with FA implant, 0.2 µg/day at 36 months (RR 3.43 95% CI 1.12 to 11.35). Conclusion: No intravitreal therapeutic regimens showed significant advantage or disadvantage with regard to efficacy. However, SOC was associated with lower risk of side effects compared to FA implants. IVTA, 4 mg, might be the best choice with lowest risk of IOP rising.